Carbon Structure of Coconut Coir Fibers - Ismail Budiman; Akhiruddin Maddu; Gustan Pari; Subyakto Subyakto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2013)
The objectives of the research was to characterize the structure of coconut coir fiber carbon. Carbonization was carried out at two successive phases, carbonization at 400 C for 300 minutes and then proceeded at 700, 800, and 900 C. In every temperature level was conducted for 45, 60, and 90 min. The structure of carbon was measured using X-ray diffraction (XRD), while the sample surface analysis was carried out using scanning electron microscopy (SEM). The results showed that the degree of crystallinity of the coconut fibers carbonized at 400 C (36.3%) was higher than uncarbonized fibers (16.36%) but lower compared to the coconut fiber carbonized at 700-900 C (41.5-59.81%). Surface analysis of samples showed that the carbonization led to the establishment and enlargement of pores in the fibers.Key words: carbon, coconut coir fiber, scanning electron microscopy, X-ray diffraction